Quantile connectedness among digital assets, traditional assets, and renewable energy prices during extreme economic crisis - Umar Kayani (17986576) (2024)
This study delves into an exploration of quantile connectedness across the domains of digital and traditional financial assets with the renewable energy prices index. The daily frequency dataset, spanning from January 02, 2018, to December 04, 2023, encapsulates diverse economic crises. Our inquiry elucidates distinctive patterns by employing empirical analyses utilizing quantile connectedness and Time-Varying Parameter Vector Autoregressive (TVP-VAR) methodologies. In this context, DeFi assets (Chain-link) emerge as the primary recipient of information shocks, while Bitcoin distinguishes itself as the preeminent transmitter of such shocks within the network. Notably, digital assets manifest heightened volatility in contrast to traditional and energy indices. Furthermore, our findings underscore that the gaming industry, specifically focusing on Non-Fungible Tokens (NFT), presents itself as the most fitting asset for portfolio inclusion. This assertion gains credence from its comparatively lower degree of connectedness with other underlying assets. These findings have significant implications for investors and portfolio managers, furnishing valuable insights into the dynamics of asset interdependencies. Consequently, this aids in cultivating a more discerning approach to investment decision-making. Other Information Published in: Technological Forecasting and Social Change License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.techfore.2024.123635